Coatings: Superhydrophilic Coating Induced Temporary Conductivity for Low‐Cost Coating and Patterning of Insulating Surfaces (Adv. Funct. Mater. 48/2016). (December 2016) - Zheng, Shuang; Wang, Dianyu; Tian, Ye; Jiang, Lei
Abstract : On page 9018, L. Jiang, Y. Tian, and co‐workers report a coating and patterning method on insulating surfaces. Glass substrates are made temporarily conductive by superhydrophilic TiO2 /SiO2 coatings and suited for electrostatic powder coating (EPC), an environmental friendly coating process widely applied to conductive workpieces. The traditional Chinese pattern of double happiness is fabricated to demonstrate this strategy.